ANALISIS EFISIENSI OPERASIONAL PERUSAHAAN FARMASI GO-PUBLIC SEBELUM DAN SESUDAH KRISIS EKONOMI DI JAKARTA - Wahyuningsih ,; Indrajaya , (Universitas Trisakti, 2006)
Efficiency is an important measurement for a company's performance. In this, we're fully aware of the importance of efficiency towards company's lifecyde, study and to describe it in analytical way, by taking 8 companies in pharmaceutical industry which are listed in Jakarta Stock Exchange. The analysis is focused on comparing the companies' efficiency before and after economic crisis hit Indonesia in 1997/1998. The data were taken from Capital Market Directory of 1996 and 2000 which related to operational and production.Using DEA method, the result shows that there are 2 efficient companies both in the year of 1996 and the year of 2000. This research summarized that there are 4 companies which increased their efficiency level, 3 companies which decreased its efficiency level, and one stagnant.Keywords : Efficiency, operational, performance